Epidemiology, Transmission, Complications, Laboratory Diagnosis & Management of Zika Virus Infection: A Systematic Review (Bangladesh Journal of Medical Microbiology, 2017)
Bangladesh J Med Microbiol 2016; 10 (1): 27-31